European week of sport: innovative initiative of European Commission that inspires children to be active - Barone R; Marino Gammazza A; Casarrubea M; De Martino L; Marino Gammazza M; Mona-chino F; Barone P; Termini F; Sammartino B; Campanella C; Di Felice V; Cappello F; et al. (The Journal of Sports Medicine and Physical Fitness, 2019)
BAC KGROU ND: Estimates indicate that more than one third of European adults are inactive, despite the known benefits of physical activity. In 2015 the European Commission launched the European Week of Sport (EWoS), to encourage people to engage in sport and physical activity. The aim of this study was to evaluate if participation in the EWoS could motivate children to participate in physical activity in future. METHOD S: A total of 10,892 children (aged 6-14), from 6 EU cities (Palermo, Italy; Ankara, Turkey; Lousada, Portugal; Gardabaer, Iceland; Rijeka, Croatia; Albacete, Spain), were enrolled in sport activities (running sport event, extra hours of physical activity, seminars on physical activity, and a family sport festival during the weekend) during the EWoS 2016. A questionnaire was set up and distributed amongst participants to identify the physical activity habits of schoolchildren and whether the activities conducted during the project were able to establish the desire to participate in physical activity. RE SUL TS: Data has shown that 15% of the individuals (respondents from the 6 countries) did not practice sport, although large variability among participating countries exists. The majority (15%) of these children showed an interest in practicing sport in ensuing months following EWoS. CO NCLU SIO NS: The results suggest that the participation in sport activities during the EWoS encouraged inactive European children to practice physical activity in the months that followed. Future researchers should however investigate whether the motivation to participate in sport observed in this study in fact became reality.